2016
DOI: 10.1111/vde.12288
|View full text |Cite
|
Sign up to set email alerts
|

Ranavirus in an outbreak of dermatophilosis in captive inland bearded dragons (Pogona vitticeps)

Abstract: To the best of the authors' knowledge this is the first report of dermatophilosis due to A. chelonae infection in lizards and the first description of a concurrent infection with a ranavirus. The combined infection associated with the skin lesions may have been the primary cause of death. Co-infection with a ranavirus should be considered as a possible factor in cases of reptilian dermatophilosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…Despite their significance, our knowledge of reptile pathogens, particularly viruses, remains limited. Indeed, to date, the only viruses known to infect bearded dragons are double-strand DNA viruses from the families Iridoviridae [ 5 , 6 , 7 , 8 ] and Adenoviridae [ 9 , 10 ], single-stranded DNA viruses from the Parvoviridae [ 11 , 12 , 13 ] and RNA viruses from the Paramyxoviridae [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their significance, our knowledge of reptile pathogens, particularly viruses, remains limited. Indeed, to date, the only viruses known to infect bearded dragons are double-strand DNA viruses from the families Iridoviridae [ 5 , 6 , 7 , 8 ] and Adenoviridae [ 9 , 10 ], single-stranded DNA viruses from the Parvoviridae [ 11 , 12 , 13 ] and RNA viruses from the Paramyxoviridae [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Marschang et al (2005) reported the first ranaviral infection in lizards. The reports of ranavirus infections in squamates have been, for the most part, restricted to groups of captive lizards, providing little evidence of the role of ranavirus infection in wild squamate populations (Stohr et al, 2013;Behncke et al, 2013;Stohr et al, 2015;Tamukai et al 2016). Although no epizootics have been reported, ranaviral DNA and seropositive animals have been detected in wild squamate populations (Alves de Matos et al, 2011, Ariel et al, 2017Goodman et al, 2018).…”
Section: -Squamata (Lizards and Snakes)mentioning
confidence: 99%
“…Maclaine et al (2018) recently demonstrated the susceptibility of an Australian lizard species (Intellagama lesueurii lesueurii) to ranaviral infection, documenting that clinical signs and histopathological changes varied with inoculation route. With increasing descriptions of ranaviral infected lizards over the last decade, an emerging trend suggests that skin lesions may be a common occurrence (Behncke et al, 2013;Stohr et al, 2013;Tamukai et al, 2016). Ranaviral infections are systemic, and there is often extensive damage to multiple organs during infection, especially the liver and spleen in reptiles.…”
Section: Pathologymentioning
confidence: 99%
“…Chytridiomycosis in amphibians, white-nose syndrome in bats, and snake fungal disease (SFD) (Ophidiomycosis) have been known as serious fungal diseases that harm ecosystems [1][2][3][4] . SFD is caused by the fungus Ophidiomyces ophiodiicola (O. ophiodiicola) 5].…”
Section: Introductionmentioning
confidence: 99%